2020
DOI: 10.1186/s40168-020-00819-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics reveals that the rumen microbiome and its metabolome together with the host metabolome contribute to individualized dairy cow performance

Abstract: Background: Recently, we reported that some dairy cows could produce high amounts of milk with high amounts of protein (defined as milk protein yield [MPY]) when a population was raised under the same nutritional and management condition, a potential new trait that can be used to increase high-quality milk production. It is unknown to what extent the rumen microbiome and its metabolites, as well as the host metabolism, contribute to MPY. Here, analysis of rumen metagenomics and metabolomics, together with seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
208
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(224 citation statements)
references
References 61 publications
13
208
2
1
Order By: Relevance
“…Overall, due to the important role of metabolism across all biological processes, metabolomics-based studies have been increasingly used to understand the physiological processes associated with economically important traits in the dairy industry, such as milk production in dairy cattle (as affected by the feeding systems) and cheese manufacturing [ 2 , 3 , 4 ]. Additionally, several metabolomic research efforts have been mainly devoted to a better understanding of the impact of diet on rumen health in dairy cows [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, due to the important role of metabolism across all biological processes, metabolomics-based studies have been increasingly used to understand the physiological processes associated with economically important traits in the dairy industry, such as milk production in dairy cattle (as affected by the feeding systems) and cheese manufacturing [ 2 , 3 , 4 ]. Additionally, several metabolomic research efforts have been mainly devoted to a better understanding of the impact of diet on rumen health in dairy cows [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the role of the rumen microbiome in host health goes far beyond the local role of the rumen. Previous studies have revealed the interaction between the diversity or unique niche of functional categories and metabolic factors that control microbial metabolism and related nutrient formation pathways ( 12 , 13 ). Accumulating evidence indicated that rumen metabolic disorders related to changes in the rumen microbiota composition are important risk factors for disease development ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using an omics-based structure have suggested that differences in rumen microbiota are associated with cattle production and health traits, such as feed efficiency [ 130 , 131 ], methane (CH 4 ) yield [ 132 ], milk composition [ 133 ], and ruminal acidosis [ 134 ]. Manipulating rumen microbiota may improve cattle productivity and health and reduce CH 4 emissions.…”
Section: Metabolic Response Of Dairy Cows To Challenges: Insights mentioning
confidence: 99%